Kampanye Public Relations Greenpeace Indonesia dalam Menangani Krisis Iklim - Hambali, Ikhsan -; Rosyidi, Imron (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This article discusses the process of Greenpeace Indonesia's public relations campaign to deal with the climate crisis through Instagram social media. This study was conducted using a descriptive qualitative constructivism approach. Source of data based on public relations informants Greenpeace Indonesia. Data collection techniques using in-depth interviews, passive participatory observation, data collection with documents. The results of this study explain that Greenpeace Indonesia's public relations campaign to handle the climate crisis through social media Instagram @greenpeaceid has gone through four main processes. 1) The process of identifying problems by looking for data and facts in the field; 2) Campaign design process by determining campaign targets; 3) the process of implementing a campaign that adheres to the results of problem identification analysis in the form of scientific data; 4) Evaluation process by looking at and assessing indicators of program implementation results.